2010
DOI: 10.2466/07.13.17.pms.110.c.1065-1074
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE AND ACCEPTANCE OF TATTOOS AND PIERCINGS: A SURVEY OF YOUNG ADULTS FROM THE SOUTHERN GERMAN-SPEAKING AREA OF CENTRAL EUROPE1

Abstract: The present study examined the prevalence and acceptance of body piercings and tattoos among a community sample from the southern Germanspeaking area of Central Europe. A total of 440 respondents completed information about their own body piercings and tattoos and reported whether they would be likely never to have piercings and tattoos in the future. Analyses indicated that 19.8 and 15.2% of respondents had piercings (excluding the earlobe) and tattoos, respectively. Women were more likely to have body pierci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(30 reference statements)
1
5
0
2
Order By: Relevance
“…In the present study, we found a rise in the population of tattooed women over the past decade. Similar trends have been noted by other authors both in Poland and other countries, although some researchers have reported a preponderance of tattooed males or similar proportions of males and females in the tattooed population (Antoszewski, Sitek, Fijałkowska, Kasielska, & Kruk-Jeromin, 2010;Armstrong et al, 2008;Braverman, 2012;Deschesnes et al, 2006;Laumann & Derick, 2006;Makkai & McAllister, 2001;Mayers, Judelson, Moriarty, & Rundell, 2002;Pajor, Broniarczyk-Dyła, & Świtalska, 2015;Quaranta et al, 2011;Stieger, Pietschnig, Kastner, Voracek, & Swami, 2010;Stirn, 2003;Swami et al, 2012;Zarębska, 2012). According to Heywood et al (2012), in Australia tattooed women outnumbered tattooed men among 20-29-year olds, while in the 40+ population the relative proportions were reversed.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we found a rise in the population of tattooed women over the past decade. Similar trends have been noted by other authors both in Poland and other countries, although some researchers have reported a preponderance of tattooed males or similar proportions of males and females in the tattooed population (Antoszewski, Sitek, Fijałkowska, Kasielska, & Kruk-Jeromin, 2010;Armstrong et al, 2008;Braverman, 2012;Deschesnes et al, 2006;Laumann & Derick, 2006;Makkai & McAllister, 2001;Mayers, Judelson, Moriarty, & Rundell, 2002;Pajor, Broniarczyk-Dyła, & Świtalska, 2015;Quaranta et al, 2011;Stieger, Pietschnig, Kastner, Voracek, & Swami, 2010;Stirn, 2003;Swami et al, 2012;Zarębska, 2012). According to Heywood et al (2012), in Australia tattooed women outnumbered tattooed men among 20-29-year olds, while in the 40+ population the relative proportions were reversed.…”
Section: Discussionsupporting
confidence: 82%
“…Welche Motivation treibt jemanden, der Körpermodifikationen nachfragt, an? Studien sprechen für spezifische Verhaltensweisen und Vorlieben von ge piercten oder auch tätowierten Menschen, die offenbar eine höhere Risiko bereitschaft aufweisen, häufiger rauchen und sexuell aktiver sind als andere Bevölkerungsgruppen (Stieger et al 2010;Rivardo u. Keelan 2010). Zu vermu ten ist das zugrunde liegende Bedürfnis, sich von der Masse abzuheben und biedere Normen zu verlassen.…”
Section: Motive: Sozialpsychologische Aspekteunclassified
“…Özellikle 1980'lerin sonlarında dövme ve piercing popülaritesi yeniden hız kazanmış ve son 30 yılda ABD, İngiltere, Fransa, Almanya ve diğer batı ülkelerinde yaygınlaşmıştır 5 . Bu konu ile ilgili yapılan çalışmalarda, adölesan döneme geçişte risk alma ve kendini ispatlama piercing taktırma nedenlerinin başında gelmekle birlikte kendini ifade etme, dini inanç, seksüel olgunluğa ulaşmanın ispatı, ayırt edilme, farklı olma, cesaret göstergesi ve moda gibi nedenler kadınlar ve erkekler arasında piercing yaygınlığını arttırmaktadır 6,[8][9][10][11] . Bununla birlikte, bu uygulamalar ile ilgili kesin bir istatistiksel veri mevcut değildir ve alınan insidans tahminleri, düşük katılımlı çalışmalardan elde edilmektedir 7,12 .…”
Section: Introductionunclassified